Propuesta para un sistema de tratamiento de aguas residuales provenientes del proceso de galvanizado por inmersión en caliente para García Vega S.A.S (2020)
A proposal is made for a wastewater treatment system from the hot-dip galvanizing process in the García Vega SAS company, for this, each of the stages of the process are evaluated, determining that the pickling, rinsing and cooling stages These are the stages that generate the greatest discharge to the effluent and fail to comply with resolution 0631 of 2015 of the Ministry of the Environment regarding the content of acidity, Zinc, Iron, Copper, Nickel and Lead. Through the technique of reduction in origin substitution of raw materials, the assembly of the process is carried out at the laboratory level to observe the stripping characteristics of Cleaner FA and Kleanex Dec products, achieving stripping 57% of the material when working at a concentration of 25 % V / V and with parts not suitable for being galvanized. From the results obtained, the treatability of the mentioned stages is carried out, where the parameters for the rinsing and cooling stages are met. For the pickling stage, it is obtained that with the substitution of raw materials the optimal treatment and removal of metals is achieved, being an excellent option for the replacement of 16% hydrochloric acid as a pickling solution. It is established that the unit operations involved in the treatment system are initial grease trap filtration, precipitation, coagulation, sedimentation and filtration, having a total cost involving labor and inputs of $ 179 492 027 (One hundred and seventy nine million, four hundred and ninety-two thousand and twenty seven COP).